Random Subgraphs of Finite Graphs: II. The Lace Expansion and the Triangle Condition - Borgs, Christian; Chayes, Jennifer; Hofstad, Remco van der; Slade, Gordon; Spencer, Joel (Annals of Probability, 2005)
In a previous paper we defined a version of the percolation triangle condition that is suitable for the analysis of bond percolation on a finite connected transitive graph, and showed that this triangle condition implies that the percolation phase transition has many features in common with the phase transition on the complete graph. In this paper we use a new and simplified approach to the lace expansion to prove quite generally that, for finite graphs that are tori, the triangle condition for percolation is implied by a certain triangle condition for simple random walks on the graph. The latter is readily verified for several graphs with vertex set [0, 1, . . . ,r − 1]n, including the Hamming cube on an alphabet of r letters (the n-cube, for r = 2), the n-dimensional torus with nearest-neighbor bonds and n sufficiently large, and the n-dimensional torus with n > 6 and sufficiently spread-out (long range) bonds. The conclusions of our previous paper thus apply to the percolation phase transition for each of the above examples.